(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The study examined the Authorship Patterns and Degree of Collaboration of Authors cited in Masters Degree Dissertations submitted to the Faculty of Education, Rivers State University, Port Harcourt. Two research objectives guided the study. It adopted an ex-post facto research design and documentary analysis methods for the study. The population of the study comprised of a total of 55 masters degree dissertations submitted to the faculty of education, randomly selected from 2016-2023, generating 5,984 articles. Hence, a checklist was designed for data collection. Data was analysed using descriptive statistics (percentages, mean average, chart). Findings indicate that single authors made the highest contribution in the field of Education as they dominated the authorship pattern with 51.67% of the sources cited. The degree of authors’ collaboration was 0.483, indicating less collaborative research in the field of Education. The study therefore recommends that; proper awareness/advocacy is needed to enlighten authors/researchers on the significance of collaborative research in the field of Education and other fields of study in order to encourage multidisciplinary approach to knowledge.